Meibomian gland alterations in allergic conjunctivitis: insights from a novel quantitative analysis algorithm - Wei, Jingting; Xiao, Kunhong; Cai, Qingyuan; Lin, Shenghua; Lin, Xiangjie; Wang, Yujie; Lin, Jiawen; Lai, Kunfeng; Ye, Yunxi; Liu, Yuhan; Li, Li (Frontiers in Cell and Developmental Biology, 2025)
PurposeTo investigate the changes in meibomian gland (MG) structure in allergic conjunctivitis (AC) patients using an intelligent quantitative analysis algorithm and to explore the relationship between these changes and clinical parameters.MethodsA total of 252 eyes from patients with AC and 200 eyes from normal controls were examined. Infrared meibography was performed using the non-contact mode of the Keratograph 5M. MG images were analyzed using a deep learning-based a quantitative analysis algorithm to evaluate gland length, area, dropout ratio, and deformation. Clinical parameters, including tear meniscus height, tear break up time (TBUT), conjunctival hyperemia, and Ocular Surface Disease Index (OSDI) scores, were assessed and correlated with changes in the structure of MG.ResultsThe average MG length in AC patients was 4.48 ± 1.04 mm, shorter compared to the control group (4.72 ± 0.94 mm). The average length of the central 5 glands in AC patients was 4.94 ± 1.67 mm, which was also shorter than the control group’s central 5 glands (5.38 ± 1.42 mm). Furthermore, the central 5 glands’ area in AC patients (1.61 ± 0.64 mm2) was reduced compared to the control group (1.79 ± 0.62 mm2). Tear meniscus height was lower in the allergy group (0.26 ± 0.10 mm) compared to the control group (0.44 ± 0.08 mm) (P < 0.05). The non-invasive first tear film break-up time was shorter in the allergy group (8.65 ± 6.31 s) than in the control group (10.48 ± 2.58 s) (P < 0.05). Conjunctival congestion was higher in the allergy group (1.1 ± 0.52) compared to the control group (0.97 ± 0.30) (P < 0.05). The OSDI score in the allergy group (8.33 ± 7.6) was higher than that in the control group (4.00 ± 0.50) (P < 0.05). Correlation analysis revealed that the gland dropout ratio was positively associated with male gender and negatively associated with age and OSDI scores. Additionally, despite an increased number of MG, tear film stability was not improved.ConclusionThrough the intelligent quantitative algorithm, we found that AC leads to significant changes in MG structure, particularly affecting gland length and central area.